The effect of differentiated learning method on students' achievement in writing skills in learning Arabic as a foreign language - Abdullah Meyad, Najiba; Roslan, Samsilah; Abdullah, Maria Chong; HajiMaming, Pabiyah (Council for Innovative Research, 2014)
Differentiated Learning is a method of teaching which has been set and used in education to meet learners’ various needs and preferences. This paper investigates the effect of Differentiated learning method (DLM) on students’ achievement in writing skills in learning Arabic as a foreign language in Malaysia. A total of 100 students (47 males and 53 females), who were randomly selected, participated in this study. The pre-and post-tests comparison groups design was used to determine if there was significant differences between the experimental and control groups. The experimental group was taught using DLM, while the control group was taught using the teacher-centered method (TCM). Descriptive statistics were used to determine the effect of DLM on students’ achievement in writing skills. The statistical results demonstrated that there was a significant difference in the post-test between the experimental group (M=10.14, SD=2.79) and the control group (M=8.20, SD= 2.38); t (3.73), p < .05). The experimental group’s achievement was generally more than the control group’s which proves that the DLM is an effective approach in improving students’ writing achievement in learning Arabic Language as a foreign language in Malaysia.